2000
DOI: 10.1200/jco.2000.18.6.1220
|View full text |Cite
|
Sign up to set email alerts
|

Does Locoregional Radiation Therapy Improve Survival in Breast Cancer? A Meta-Analysis

Abstract: Locoregional radiation after surgery in patients treated with systemic therapy reduced mortality. Several questions remain on how these results should be translated into current-day clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
179
1
12

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(200 citation statements)
references
References 46 publications
8
179
1
12
Order By: Relevance
“…The mean follow-up was 8 years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Five patients were lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The mean follow-up was 8 years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Five patients were lost to follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Postmastecomy chest wall radiotherapy (PMRT) is a common treatment modality for high‐risk breast cancer patients following mastectomy because it has been shown to improve local control and survival 1 , 2 , 3 . The RTOG breast atlas (4) defines the chest‐wall target volume as extending cranially to the caudal border of the clavicle head, caudally to the loss of computed‐tomography (CT) apparent contralateral breast, laterally to the mid‐axillary line, medially to the sternal‐rib junction, posteriorly to the rib‐pleural interface, and anteriorly to the skin.…”
Section: Introductionmentioning
confidence: 99%
“…It should, however, be noted that in this series, patients treated with exclusive or preoperative radiotherapy fared worse in terms of locoregional control than others, perhaps also because of a selection of patients with poor prognosis. This opens the debate as to whether radiotherapy could not play a role in increasing the rate of breast-conserving treatments for some invasive carcinomas, as it is an important part of the treatment of large breast cancers (Whelan et al, 2000;Clarke et al, 2005) and has been shown to achieve complete clinical response (6 -41%) with doses compatible with planned secondary surgeries (Calitchi et al, 1991;Scholl et al, 1994;Broet et al, 1999;Bollet et al, 2006). At the Institut Curie, the S6 trial randomised premenopausal women between chemotherapy and radiotherapy as an initial treatment for large breast cancers (Scholl et al, 1994).…”
Section: Discussionmentioning
confidence: 99%